Interes in upravičenost zavarovalnic do vpogleda v medicinsko dokumentacijo svojih zavarovancev - Vrabl, Miran (Zdravniški vestnik, 2008)
Background Insurance is a contractual relationship between parties with mutualfinancial interest. In order to calculate risks and premium amounts and indubitably determine the scope of a loss event, insurance companies need complete medical documentation of their insureds. In the insurance applicationform the insured undertakes to submit to the insurance company all required documentation and authorises the insurance company to obtain such data. The Insurance Act enables insurance companies to obtain medical documentation of their insureds from all medical and other institutions also in cases when an insured who has filed an insurance claim is opposed to that. An insight into medical documentation of the insured is guaranteed by numerouslegal bases. Often an insured refuses to submit to the insurance company the required medical documentation in spite of filing an insurance claim, which prevents the insurance company from making a decision on compensation. Medical certificates by no means represent an adequate substitute for photocopies of outpatient records, since the insurance company is the one to decide which medical data are relevant for solving a particular claim. Contrary to the Personal Data Protection Act, the Insurance Act, the Act on Patientsć Rights and the Code of Obligations, some medical institutionsrefuse to submit the required medical documentation to insurance companies, unless the insured signs a special authorisation for this purpose. Such procedures are contrary to the authorisation of the insured given to the insurance company upon taking out the insurance as well as to the legislative regulations specified above. (Abstract truncated at 2000 characters)
Keywords: Confidentiality; Insurance, Health; Legislation And Jurisprudence; Legislation, Medical; Medical Records; medicinska dokumentacija; Medicinske kartoteke; Zakonodaja medicinska; Zaupnost; Zavarovanje zdravstveno; zdravstveno zavarovanje